Automated Monitoring System for Rainwater Harvesting Tank at Telkom University - Sugesti, Erna Sri; Hartaman, Aris; Adam, Kharisma Bani; Dewanata, Deni Wahyu; Latief, Noval Ramadhana; Sularto, Rafi Fadyan Ananda; Marbun, Jeremia Jordan; Umbara, Taufan (Universitas Diponegoro, 2024)
The use of ground tank constructed by Telkom University for Rainwater Harvesting (RWH), is limited to environmental maintenance due to concerns regarding the quality of water in the underground tank. Therefore, this research aims to develop a remote monitoring device that uses Internet of Things (IoT) technology to monitor the pH, water surface, submerged materials, and water clarity levels in ground tank. To achieve the requirements, pH, ultrasonic-based volume, Total Dissolved Solids (TDS), and Turbidity sensors were selected due to the IoT connectivity. The enabling device, namely the ESP 32 microcontroller and Blynk platform were installed on monitoring dashboard on a tablet computer with 4GB of RAM. The result showed that calibration of each sensor had good accuracy, except for the Turbidity sensor due unavailable materials. In conclusion, the RWH monitoring system is suitable for use.